Evaluation of the Accuracy of Mammography, Ultrasound, and Mri in Diagnosing Breast Cancer at King Saud Medical City - Shaber, Salman Saad Bin; Mohtasib, Rafat; Alamri, Nadia Diab; Altheyab, Haya Ibrahim; Hadi, Shoroq Abduljalil; Alriyaee, Afyaa Abdullah; Maghfuri, Amani Hamid; Ahmed, Fayka Karem; Shabr, Abdullah Saad Bin; Alhamdan, Faisal Fahad (Journal of Posthumanism, 2025)
This study evaluates the diagnostic accuracy of mammography, ultrasound, and magnetic resonance imaging (MRI) in detecting breast cancer at King Saud Medical City. A retrospective cohort design was employed to analyze medical records from 168 patients with BI-RADS 4/5 lesions diagnosed between 2021 and 2023. The primary objective was to assess the diagnostic accuracy of each imaging modality against histopathology results. Findings indicate that MRI demonstrated the highest accuracy at 91.7%, followed by mammography at 87.5% and ultrasound at 88.1%. These results underscore the importance of a multimodal imaging strategy for enhancing precision in breast cancer detection, leading to improved diagnostic accuracy and better patient outcomes.